Menumbuhkan Minat dan Keterampilan Berolahraga melalui Pembelajaran PJOK di Sekolah Dasar - Putri, Ajeng Adistya; Ridhwan, Andrea Syahla Nathaniela; Zahra, Fanya Rachma; Handayani, Nur Afifah; Maharani, Nadia Fitri; Rahmadini, Rizqia; Mulyana, Agus (Indo-MathEdu Intellectuals Journal, 2024)
Physical Education, Sports, and Health or PJOK in Elementary Schools (SD) has a very important role in fostering interest and skills in sports among elementary school age children. The purpose of this article is to find out how PJOK learning in elementary school can increase children's interest and sports skills, influencing factors, and effective solutions to increase children's interest and sports skills through PJOK learning in elementary school. The approach used in this article is a qualitative approach through the literature study method. Data collection is carried out by collecting various relevant references and updates, including research articles published through google scholar, books, and other documents that are relevant to the substance of the problem in this study. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that in recent years, the interest of elementary school students in sports has decreased. Various factors can cause this, such as lack of facilities, teachers who have many tasks outside of class hours, to educators who tend to be lazy to do physical activities. To increase students' interest and skills in PJOK, several strategies can be applied including motivating students by helping to develop and direct students' potential, providing opportunities to develop creativity, providing awards, and providing guidance and motivation